ANALISIS KEAMANAN FILE SERVER BERBASIS LINUX TERHADAP AKSES TIDAK SAH - Rakhmadi Rahman; Nurfaida Nurfaida; Muhammad Hasyim Rusmin (Jurnal Riset Sistem Informasi, 2026)
In organizational environments, file servers function as centralized platforms for data storage and sharing, making system security a critical requirement. Inadequate security configurations may increase the risk of unauthorized access and data breaches. This study analyzes the security of a Linux-based file server through experimental testing of layered security mechanisms. The experiment was conducted on an Ubuntu Server configured with Samba and Network File System services. The applied security mechanisms include user and group management, Discretionary Access Control, Mandatory Access Control using AppArmor, and network access restrictions through a firewall. Security evaluation was performed using authorized and unauthorized access scenarios, including network scanning and authentication attempts. The results demonstrate that implementing layered security mechanisms significantly enhances protection against unauthorized access compared to basic permission settings alone. This research contributes practical guidance for strengthening Linux file server security in organizational environments.